Efektivitas Penerapan Sistem E-Court Pengadilan Agama Pelaihari dalam Perkara Harta Bersama - Maulana, Ahmad (Fakultas Hukum Universitas Primagraha, 2025)
This study analyzes the effectiveness of the implementation of the e-court system at the Pelaihari Religious Court in joint property cases and identifies the influencing factors. In the digital era, the demand for judicial efficiency and transparency creates an urgency to review the implementation of this system, given the challenges such as the public's lack of understanding of online services. The research uses an empirical legal method with a legal anthropology approach. Data was obtained from primary data (interviews) and supported by secondary data from related literature. The results show that the implementation of e-court at the Pelaihari Religious Court is already effective, as all indicators of effectiveness have been met. This study is expected to contribute data on e-court in joint property cases and serve as evaluation material for judicial institutions in Indonesia